Digital Single Market as the new world to the European Union: repercussions in social and institutional regulatory structure – the universal service and the Body of European Regulators for Electronic Communications’ (BEREC) redefinition - Abreu, Joana Covelo de (2018)
Digital Single Market is the new world in the EU and it is perceived as primary public interest because it was one of the ways the EU found to become more financially attractive and better suited to innovation. To accomplish that, several legal solutions appear to be unsuitable for the present time EU is living in. Concerning electronic communications, its legal and regulatory framework needed to be recasted and a new Electronic Communications Code proposal was made by the European Commission. Among many innovative solutions, it aims at redefining EU universal service, to update it to connectivity solutions of our time, and at revising the Body of European Regulators for Electronic Communications’ role, granting it further competences on crossborder dispute resolution and articulation between European institutions and national regulatory authorities. These dimensions rethink both social and institutional regulatory framework and this text wants to understand what their strengths and weaknesses are.